Bentuk Kesopanan Wakimae (Tinjauan Semiotik) pada Tokoh Demiurge dari Anime Overlord Karya: Kugane Maruyama - Suhada, Muhammad Azhar; Sukmara, Rina (Jurnal Bahasa Jepang Taiyou, 2023)
Wakimae is a term that has elements of values or norms that are more about social norms using formal forms. Wakimae can also be interpreted as a form of politeness such as a formula for speaking or conveying something by paying attention to the value of one's status, for example how to speak or communicate to a friend when compared to a boss will be very different when viewed from the speech and attitude that must be done. This journal was made, to find out how the spoken language of the Demiurge character in the form of Wakimae politeness in the Overlord Anime, and to find out the gestures of the Demiurge character. By using descriptive qualitative methods. The data collection technique used is documents. The results of this study are the form of Wakimae politeness in the Demiuerge character and how his body gestures.